1998
DOI: 10.1063/1.367231
|View full text |Cite
|
Sign up to set email alerts
|

Band discontinuities and local interface composition in BeTe/ZnSe heterostructures

Abstract: Using photoelectron spectroscopy, we have investigated the band alignment at the interface of pseudomorphic BeTe/ZnSe(100) heterojunctions for different interface terminations. The heterostructures of high structural quality have been produced by molecular beam epitaxy; the interface termination was adjusted by variation of the growth parameters between the growth process of ZnSe and BeTe. The valence band offset for a Zn-rich BeTe/ZnSe interface is determined to be 1.26±0.15 eV, for the Se-rich BeTe/ZnSe inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
16
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…We find that the band offset between the nearly lattice-matched ZnSe and BeTe is independent of the interface composition, which is consistent with a recent theoretical study, 8 but in contrast with previous reported data. 7 Furthermore, we show that ZnX always has higher natural VBM than BeX and MgX due to anion p-cation d repulsion, which is consistent with previous understanding of the general chemical trends of the band offset in semiconductors. 2 However, epitaxial strain could reverse the sign of the band offset.…”
supporting
confidence: 83%
See 1 more Smart Citation
“…We find that the band offset between the nearly lattice-matched ZnSe and BeTe is independent of the interface composition, which is consistent with a recent theoretical study, 8 but in contrast with previous reported data. 7 Furthermore, we show that ZnX always has higher natural VBM than BeX and MgX due to anion p-cation d repulsion, which is consistent with previous understanding of the general chemical trends of the band offset in semiconductors. 2 However, epitaxial strain could reverse the sign of the band offset.…”
supporting
confidence: 83%
“…6 In addition to the technological importance, these unconventional II-VI compounds also show some interesting, but unexplained, physical phenomena. For example, recent photoelectron spectroscopy measurements of Nagelstrasser et al 7 show that ⌬E v at the BeTe/ZnSe interface is highly dependent on the interface composition and can vary by as much as 0.8 eV. Subsequent ab initio pseudopotential calculations of Bernardini et al 8 show that the experimentally proposed valence band offset cannot occur in the nominal BeTe/ZnSe interface.…”
mentioning
confidence: 96%
“…Such hole localization has been already suggested from the analysis of photoluminescence (PL) under high optical excitation conditions [7]. One of the possible mechanisms of the localization could be band bending at the ZnSe-BeTe interface which is presented in these structures as it follows from photoemission spectroscopy [8]. To confirm this idea we have studied PL spectra of ZnSe/BeTe short-period superlattices with the layer thickness 40 Å/20 Å, where the hole wave function spreads through both interfaces.…”
mentioning
confidence: 99%
“…2͑a͔͒. The reduction of conduction band offset 5,13 together with the change of effective well thicknesses caused by the interdiffusion result in the shift of ISB absorption to the lower energy ͑longer wavelength͒ ͓Fig. 2͑b͔͒.…”
mentioning
confidence: 98%
“…12 For example, to make a waveguide structure, the top cladding layer, 1 -2 m Zn x Mg y Be 1−x−y Se quaternary layer, is grown for about 3 h at 300°C, which is significantly higher than the temperature used for the growth of the QW region. 13,14 Thermal annealing ͑TA͒ can lead to interdiffusion and the formation of interfacial layers between the barriers and the wells. At the same time, annealing may change the carrier density in the well layers due to the reduction or increase of compensation centers.…”
mentioning
confidence: 99%